Performance evaluation of a small animal PET scanner a high level of multiplexing and charge-signal transmission. (18th February 2019) - Lee, Sangwon; Choi, Yong; Jung, Jin Ho; Jung, Jiwoong; Kim, Kyu Bom; Choe, Hyeok-jun; Leem, Hyun Tae; Lee, Hwunjae; Huh, Yong-Min
Abstract: Small animal positron emission tomography (PET) is a noninvasive imaging modality that enables in vivo imaging and quantification of the biological processes of small experimental animals. We have developed a small animal PET that utilizes a high-resolution multiplexed readout and charge signal transmission (CST) method. The small animal PET was composed of six detector blocks consisting of SiPMs and LYSO arrays. Six detector blocks were mounted on a PET gantry having an inner diameter of 76 mm, outer diameter of 112 mm, and axial length of 40.8 mm. The charge signals of SiPM output were transmitted to the input of multiplexed readout using 4 m flexible flat cables. The multiplexed readout was composed of six main boards, each of which included 36 detector boards, to reduce the number of readout channels by a factor of 36, with a multiplexing ratio of 144:4. The performance of the small animal PET was evaluated using NEMA NU 4-2008 standards, and its imaging capability was demonstrated by in vivo mouse imaging studies. The average energy and time resolutions were 13.2%  ±  0.3% and 3.8 ns, respectively. The spatial resolution at the center of the transaxial FOV was 1.1 mm, and the peak sensitivity at the center of the axial FOV was 1.5%. The peak noise equivalent count (NEC) rate and scatter fraction were 21.1 kcps at 18.2 MBq and 21%, respectively. The acquired images demonstrated high quality tracer uptake patterns of small experimental animals. The results of performance evaluation and animal imaging indicate that the small animal PET developed in this study can provide high-quality small animal imaging with cost-effectiveness and compactness.